Pilot program for integrated development in Afghanistan: May 2002-April 2003 - BRAC (© BRAC, 2016)
1. Afghanistan 2. BRAC 3. Micro finance programme 4. Employment and income generation 5. BRAC education programme 6. BRAC health programme 7. proposed activities in Afghanistan